2018
DOI: 10.3389/fimmu.2018.02909
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of the Tumor Microenvironment: Turn Foe Into Friend

Abstract: Immunotherapy, where the patient's own immune system is exploited to eliminate tumor cells, has become one of the most prominent new cancer treatment options in the last decade. The main hurdle for classical cancer vaccines is the need to identify tumor- and patient specific antigens to include in the vaccine. Therefore, in situ vaccination represents an alternative and promising approach. This type of immunotherapy involves the direct intratumoral administration of different immunomodulatory agents and uses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
156
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(165 citation statements)
references
References 194 publications
(198 reference statements)
2
156
0
Order By: Relevance
“…Systemic administration of mCelyvir was followed by changes in the TME, more remarkable in the spontaneous model than the induced one. After treatment, TME showed a less pro-tumoral and more inflammatory profile, a scenario that contributes to create a more proimmune local situation for an antitumor immune response, as has been previously described [33,34]. Today it is well accepted the immunomodulatory role associated to oncolytic virotherapy through several secondary mechanisms derived from the tumor cell infection itself [6].…”
Section: Discussionmentioning
confidence: 67%
“…Systemic administration of mCelyvir was followed by changes in the TME, more remarkable in the spontaneous model than the induced one. After treatment, TME showed a less pro-tumoral and more inflammatory profile, a scenario that contributes to create a more proimmune local situation for an antitumor immune response, as has been previously described [33,34]. Today it is well accepted the immunomodulatory role associated to oncolytic virotherapy through several secondary mechanisms derived from the tumor cell infection itself [6].…”
Section: Discussionmentioning
confidence: 67%
“…Several studies have reported that the effectiveness of immunotherapies depends on reactivating the host immune response of the tumor immune microenvironment (TME) . However, the TME, which comprises immune cells, vessel cells, fibroblasts, and the extracellular matrix, is diverse across tumor patients, and different TME patterns can drive wither tumor repression or progression . As described in a previous study, patients with a “hot” or highly infiltrated TME have more preexisting immune reserves, suggesting that ICI‐based monotherapy will likely be effective for these patients, but patients with a “cold” or non‐infiltrated TME always lack preexisting immune reserves, indicating that ICIs alone will not be sufficient .…”
Section: Introductionmentioning
confidence: 92%
“…For response strati cation and ideal patient selection, it is necessary to detect the tumor PD-L1 expression level. It is worth noting that the tumor cells are surrounded by a homeostatic and dynamic TME that involves many uncertain factors including cytokines secretion, hypoxia, in ammation and treatment responses, and changes in one of these factors affects tumor PD-L1 expression [14]. Hence, it is suspicious to determine PD-L1 expression on tissue samples by immunohistochemical (IHC) analysis, and a more effective PD-L1 detection method is urgently required.…”
Section: Introductionmentioning
confidence: 99%